Managemet of oil palm bunch moth (Tirathaba mundella walker) in young mature oil palm plantation on peat soil in Sarawak, Malaysia - Su, Chong Ming (2016)
The oil palm bunch moth, Tirathaba mundella is one of the most important pests for oil palm planted in peat. Chronic outbreak of this pest is getting more pronounced in recent years when more peat lands were being cleared for oil palm in Sarawak. When proper control measures were not in place, the outbreak would cause a significant reduction on oil palm early yield. The results of three rounds field ablation demonstrated that percentages of new infested bunches in ablated fields were significantly higher (41.63%, 13.24%, 7.68%) than non ablated fields (17.21%, 4.78%, 4.55%), which is the control at week 20, week 28 and week 36 respectively. This suggested that it is not justifiable for oil palm growers to carry out field ablation as cultural control practice against oil palm bunch moth, T. mundella in young mature oil palm plantation as commonly believed. Further studies were being conducted to evaluate the effectiveness of seven insecticides namely Bacillus thuringiensis, Flubendiamide, Chlorantraniliprole, Pyridalyl, Fipronil, Cypermethrin and Flufenoxuron on controlling oil palm bunch moth, T. mundella in a young mature oil palm plantation. Two insecticides namely Chlorantraniliprole and Flubendiamide outweighed the other conventional and biological insecticides in controlling oil palm bunch moth, T. mundella with significantly higher percentages of uninfested bunches with their effectiveness stretching to six months after treatment. These treatments also showed significantly lower percentages of new infested bunches, old infested bunches and number of larvae count within the monitoring period. The effect of controlling T. mundella using biological insecticide, Bacillus thuringiensis, which was the conventional practice in the oil palm plantation were inconsistent and fluctuated across all the parameters studied. This study also assessed the detrimental effects of selected insecticides on oil palm natural pollinators, Elaeidobius kamerunicus. Out of eight insecticides namely Flubendiamide, Chlorantraniliprole, Dinotefuran, Fipronil, Cypermethrin, Flufenoxuron, Pyridalyl and Indoxacarb which were selected for the study, only three insecticides were found to have detrimental effects on E. kamerunicus. The mean number of newly emerged adult E. kamerunicus obtained from male inflorescences treated with Dinotefuran, Fipronil and Cypermethrin were only 0.58, 4.74 and 6.05 respectively. This is significantly lower as compared to other insecticides namely Bacillus thuringiensis (56.31), Flubendiamide (19.72), Chloratraniliprole (23.61), Flufenoxuron (36.96), Pyridalyl (30.93), Indoxacarb (38.16) and control (43.06). The effectiveness of the six E. kamerunicus friendly insecticides on controlling oil palm bunch moth, T. mundella were then evaluated in the follow-up study where one round of field ablation was incorporated before the insecticides treatment. The results of the study suggested that there were no additional benefit in conducting one round of field ablation before the insecticide application in controlling T. mundella. Among the six insecticides which were found to be safe for oil palm pollinators, Chlorantraniliprole and Flubendiamide demonstrated the best control results throughout the six months monitoring period with only two rounds of spraying at 14 days interval. From these studies, it is recommended that young mature oil palm fields with severe T. mundella infestation can be controlled most effectively with two rounds of Chloratrniliprole at 14 days interval. These should be followed by two rounds of Flufenoxuron at 14 days interval, after 3 months of the second spraying of Chlorantraniliprole. With these practice, the control of oil palm bunch moth can be effectively sustained for six months without affecting the survival of oil palm pollinators. This is very crucial to achieve sustainability of oil palm production for young mature plantation.